Dinamika Psikologis Untuk Berhenti Merokok Warga Muhammadiyah Kecamatan Kalasan Sleman - Casmini Casmini (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2014)
To stop smoking is difficult. This qualitative research describes psychological dynamics of five smokers of Muhammadiyah members in responding thefatwa ofthe Majelis Tarjih and Tajdid Muhammadiyah that smoking is haram. The data were collected using in-depth interviews and using projective test, Sentence Completion Test (SCT). The projective test was conducted to 25 respondents. The results describe how difficult to change habit from smoking to not-smoking. Smoking fatwa has been received on the plains of cognitive and affective but not yet at the level of behavior. For example, smokers began to think to quit smoking andfeel uncomfortable againstfellow members of the Muhammadiyah. Keywords: psychological dynamics, stop smoking